(untitled) (Indian Journal of Child Health, 2021)
Introduction: Reduced growth velocity and delayed pubertal spurt are seen in Type1 diabetes mellitus and are influenced by a variety of factors. Objective: The objective of the study was to study various factors affecting linear growth in children with Type1 Diabetes. Methods: Age at diagnosis, auxological parameters, and hemoglobin A1c (HbA1c) were recorded from 116 children enrolled in the diabetic clinic. Results: Of 116 children, female to male ratio was 1:0.75. Mean age at diagnosis was 6.3±2.87 years. About 31.9% of children had early age of onset of diabetes (before 5 years). Majority (94.8%) had a normal height at diagnosis. At 1 year of follow-up 44% of children (38% males and 48.5% females) showed a decline in linear growth. About 48.3% of children presented initially with diabetic ketoacidosis (DKA). Only 10.7% of children with DKA at diagnosis had growth faltering. Mean age of diagnosis for those without and with growth faltering was 5.6±2.8 years and 7.3±2.6 years, respectively. Mean HbA1c for those with growth faltering and without growth faltering was 10.03±1.80 and 8.34±1.07, respectively. In 5–9.9 year age group, mean height velocity for children with better and poor glycemic control was 6.67±1.0 and 5.58±1.59, respectively; and in 10–14.9 year age group, it was 6.18±1.26 and 5.58±1.59, respectively. Conclusion: Majority of the children had normal height at diagnosis. Growth faltering was less common in children who presented with DKA at diagnosis. Children who were diagnosed at a younger age had less growth faltering. Good glycemic control was associated with better linear growth.